Kinetic and metallographic study of oxidation at high temperature of cast Ni 25Cr alloy in water vapour rich air. (September 2015) - Aranda, L.; Schweitzer, Th.; Mouton, L.; Mathieu, S.; Rouer, O.; Villeger, P.; Berthod, P.; Conrath, E.
Abstract : The high temperature oxidation behaviour of a Ni–25 wt-%Cr alloy in air enriched with water vapour (180 mbars H2 O) was studied at 1000, 1100, 1200 and 1300°C. The oxidised samples were characterised by X-ray diffraction, electron microscopy and wavelength dispersion spectroscopy. The obtained data were compared to the ones earlier obtained for the same alloy oxidised in dry air. Water vapour globally induced at all temperatures a decrease of the parabolic constant Kp and an increase in the chromia volatilisation constant Kv . The oxide scales do not present morphologic difference between the two atmospheres. After oxidation in humidified air the scale thickness is thinner and the Cr depleted depth is lower than in dry air.